Dietary changes associated with an intervention to reduce sedentary behavior in women - Casey, Kelsey M. B. (Kansas State University, 2016)
Evidence from physical activity interventions suggests that women, in particular, may overcompensate for exercise energy expenditure by increasing caloric intake. Sedentary behavior and poor diet quality are independent risk factors for many major chronic diseases including cardiovascular disease (CVD). It is unknown whether insufficiently active women alter dietary quality or caloric intake when participating in an intervention to reduce sedentary behavior. Insufficiently active women (n=49) working full-time sedentary jobs were randomized into one of two 8-week sedentary interventions occurring during the work week [short breaks (SB) (1-2 min every half hour, n=24) or long breaks (LB) (15 min twice daily, n=25)]. Dietary information was collected through 3-day food records at baseline, week 4 and week 8. Dietary quality was assessed using the Alternative Healthy Eating Index 2010 (AHEI-2010). CVD risk factors (systolic and diastolic blood pressure (BP), fasting cholesterol, triglycerides, and blood glucose, and body mass index) were assessed at baseline and week 8. For all participants there were no changes in AHEI-2010 scores over time (baseline: M=53.4, 95% CI [49.2, 57.6], week 4: M=50.3, 95% CI [45.9, 54.7], week 8: M=48.4, 95% CI [44.1, 52.7], p>0.05). Average caloric intake in the SB group (baseline: M=1943.8 kcals/day, 95% CI [1716.2, 2171.5], week 4: M=1728.8 kcals/day, 95% CI [1462.4, 1995.2], week 8: M=1616.8 kcals/day, 95% CI [1450.2, 1783.4]) decreased significantly from baseline to week 4 (p=0.015) and baseline to week 8 (p=0.002). There were no significant changes in caloric intake in the LB group (p>0.05) at either time point. In all participants, absolute changes in LDL were positively correlated with absolute changes in caloric intake (r=0.473, p=0.005). There were no other significant associations between changes in dietary quality or caloric intake with changes in any other CVD risk factor (p>0.05). Following an 8-week sedentary intervention in the workplace, insufficiently active women did not alter their dietary quality, but decreased caloric intake. Future research should explore sedentary interventions compared to physical activity interventions in women as a means to create negative energy balance, as sedentary breaks throughout the day may be effective for improving health outcomes.
Keywords: Reduced sedentary behavior; Insufficiently active women; Alternative healthy eating index 2010; Dietary qualityNutrition